Tourist Behaviour of Junior High School Students of the Selected Voivodeships in Poland: the Sociodemographic Context - Lubowiecki-Vikuk, Adrian P.; Podgórski, Zbigniew (Quaestiones Geographicae, 2016)
Leisure-time behavior, including tourist activity among contemporary adolescents has raised great interest of scientists and the representatives of the tourism industry. Not only it is important to estimate the rate of tourism activity among adolescents, but also it is necessary to bear in mind the analysis of behavior shaped on account of their gender, place of residence, or level of education. An attempt to conduct such a study was made on the basis of survey data obtained within the group of 1,067 junior high school students of the selected voivodeships in Poland. The results obtained clearly indicate that almost 1/4 of the students surveyed had not participated in tourist trips. This was particularly noticeable in the case of boys and students living in rural areas. it is important to take broader steps to stimulate young people’s needs for tourism and sightseeing. First of all, from the family which is considered a social institution, it is expected to raise young generations in the spirit of tourism and active leisure. Family’s contemporary problems: increasing poverty, or even its (partial) marginalization are commonly disregarded. A systemic approach (support for families by schools, social organizations, and government units) appears to be a successful solution, but it is a long-term and complex process.